(untitled) (Journal of the College of Basic Education, 2022)
This research revolves around (the subversive role of the Jews in the early days of Islam), where I divided this research into three topics.In the second topic, I dealt with: the position of the Messenger (PBUH) towards the Jews, where it touched on the warning and fear of the Messenger (PBUH) of the Jews, and their role in the Battle of Badr, in the Battle of Bani Qainuqa, in the Battle of Bani Qureida, and in the Battle of Khaybar.In the third topic, it dealt with: the role of the Jews in the emergence of extremist groups, where it touched on the role of the Jews in the emergence of extremists, the political intrigue of the Jews, the distortion of the Jews to intercession, the birth of extremist sects, the emulation of some Jewish Muslims, the role of the Jews in worshiping idols, and the role of the Jews in the emergence of anthropomorphism .And it is an important topic for several reasons, we were briefed on the backgrounds of some Islamic sects or affiliated with Islam, and the Jewish fingers were found behind some sects through their founders who belonged to that religion before Islam, and it is no secret that many of them used to hide their previous beliefs or show them with an Islamic template, so we see patchwork ideas Hybrids and the spread of Israeli women in some Islamic books.